A Note on Proximate Composition of Tuna Fish Paste from Minicoy - Valsan, A P; Kandoran, M K; Rao, S V Suryanarayana (Fishery Technology, 1964)
An indigenous method of preparing fish paste from Tuna fish, exclusively practiced in Minicoy island is described. Detailed proximate analysis data of the product is presented and it has been compared with the values obtained for similar products of foreign countries. A chromatographic study is also carried out for essential amino acids and also with special reference to detecting any possibilities of histamine poisoning, especially in view of the reported high values of histidine in Tuna meat. However free histamine is not detected in the sample.